Partnerships in highlands of Rwanda under integrated agricultural research for development (IAR4D) arrangements - Ngaboyisonga, C.M.; Oduol, J.; Mugabo, J.; Tenywa, M.M.; Nyamwaro, Sospeter S.; Buruchara, Robin Arani; Fatunbi, A.O.; Adekunle, A.A. (African Journals Online, 2017)
The Integrated Agricultural Research for Development (IAR4D) concept was proposed to respond to the failures of Agriculture Research and Development (ARD) systems in Sub-Saharan Africa. The key element of implementation and success of IAR4D was action sites called agricultural Innovation Platform (IPs) and their counterfactual sites. Social Network Analysis (SNA) is used to explain social relationships and partnerships. This study explored the patterns of agricultural partnerships among stakeholders in the highlands of Rwanda under IAR4D. Data were collected in action sites that included Mudende, Gataraga, Remera and Rwerere; and in their counterpart counterfactual sites that comprised of Bigogwe, Nyange and Gacaca. Results showed that in action sites, stakeholders were linked to different and diversified partners. Furthermore, many stakeholders were connected to several partners through agricultural partnerships, hence creating complex social networks with high density and degree of distribution. In the counterfactual sites, however, stakeholders were exclusively linked to the same kind of partners, and one stakeholder was connected to one partner through probably non-agricultural partnerships. These facts demonstrated that IAR4D created dense interfaces, significantly improved the networking system, and delivered technologies and innovations.